Booster Organik Tanaman Padi sebagai Program Ketahanan Pangan Kelompok Tani Margo Raharjo Desa Jatiluhur Kecamatan Karanganyar Kabupaten Kebumen - Fadjeri, Akhmad; Muflih, Ghufron Zaida; Sangadah, Siti; Suyatiningsih, Suyatiningsih; Astuti, Tri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Educating the community by conducting counselling, training and mentoring to farmer groups, as a form of supporting the food security programme in Kebumen district. Together with the Margo Raharjo farmer group in Jatiluhur village, Karanganyar sub-district, making organic boosters for rice plants. Participants involved in the service were members of the Margo Raharjo farmer group, and KKN students from Ma'arif Nahdlatul Ulama University Kebumen. Training and counselling activities are carried out so that farmers are not dependent on inorganic fertilisers while providing education on the importance of using organic materials in agriculture. This activity seeks to help overcome the problems that exist in the community, especially in the knowledge of organic fertiliser for rice plants. The use of organic boosters is not only environmentally friendly but also reduces the cost of purchasing booster products on the market which cost up to 230 thousand rupiah. Inorganic booster products are certainly very expensive and less environmentally friendly. Booster is a liquid organic fertiliser whose nutrients play a role in stimulating the generative growth of flowers and fruits. Increasing farmers' awareness of the dangers of continuous use of inorganic fertilisers encourages farmers to switch to the use of environmentally friendly organic fertilisers. Organic booster made from fermented pineapple is one of the liquid organic fertilisers applied in the generative phase of plants, namely at the beginning of flowering and fruiting. After the practice of making organic booster, participants are expected to be able to independently or together with the group to follow up and apply the fertiliser to rice plants according to instructions and recommendations. Further testing and research is needed on organic boosters and making organic boosters from different materials and easily obtained in the surrounding environment. From the results of this activity, the following conclusions were obtained: This activity can improve skills and increase knowledge or insight into the community about organic fertiliser to support increased agricultural productivity, The use of organic booster as one of the solutions to reduce the use of inorganic fertilisers to increase the productivity and quality of products from rice cultivation. Keywords: Organic Fertiliser, Liquid Organic Fertiliser, Vegetable Fungicide, Organic Rice